Determination of optimal hierarchical fuzzy controller parameters according to loading condition with ANN - Caner, Murat; Umurkan, Nurettin; Tokat, Sezal; Uestuen, Seydi Vakkas (PERGAMON-ELSEVIER SCIENCE LTD, 2008)
This paper represents an artificial neural network (ANN) backpropagation algorithm is used to choose best coefficients of hierarchical fuzzy power system stabilizer (HFPSS). PSS is used for stability enhancement of a single machine infinite bus (SMIB) power system. ANN algorithm is used to predict load condition of the power system. And according to the predicted load condition ANN determinates choosing optimal parameters of the hierarchical fuzzy controller (HFC) to achieve better performance. Simulation results are compared with conventional PSS (CPSS) to show the effectiveness of the proposed controller. Also quantitative criterias of measuring performance is computed for 16 loading conditions. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: excitation control; power system stabilizer; hierarchical fuzzy control; POWER-SYSTEM STABILIZER; ALGORITHM; DESIGN; Computer Science; Engineering; Operations Research & Management Science